ANALISIS KINERJA KEUANGAN BANK MUAMALAT INDONESIA (BMI) TAHUN 1994-1998 DAN TAHUN 1999-2003 - Muharam, Harjum; Handayani, Suyati (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2005)
Using paired sample t-test this research analyze financial performance of Bank Muamalat Indonesia between 1994-1998 and 1999-2003. Profitability ratios, liquidity tsuos, solvability ratios, and commitment to economy and Moslem community ratio are used as financial performance. The results show there are no significance different financial performance during 1994-1998 and 1999-2003 period exceptÂ commitment to economy and Moslem community ratio.